Tailored Treatment Based on Helicobacter pylori Genetic Markers of Resistance Is Associated With Higher Eradication Success. (11th February 2023) - Cummings, Linda C.; Hojat, Leila S.; Nguyen, David C.; Stempak, Lisa M.; Rhoads, Daniel D.; Sadri, Navid
Abstract : INTRODUCTION: Increasing antimicrobial resistance with Helicobacter pylori infection has focused efforts to tailor eradication therapy based on identifying genetic markers of resistance to predict antimicrobial susceptibility. METHODS: In this retrospective study, we report the effect of routine inclusion of antimicrobial susceptibility testing and recommendations for eradication therapy with gastric specimens with H. pylori . RESULTS: The use of a recommended treatment regimen based on genetic markers of resistance was associated with an 84% rate of eradication success and 4.4 greater odds of eradication relative to unrecommended treatment. DISCUSSION: This is the first study describing the use of H. pylori genetic resistance testing as standard of care.